2003
DOI: 10.1590/s0034-89102003000500002
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary HIV counseling and testing during prenatal care in Brazil

Abstract: ObjectiveVoluntary HIV counseling and testing are provided to all Brazilian pregnant women with the purpose of reducing mother-to-child HIV transmission. The purpose of the study was to assess characteristics of HIV testing and identify factors associated with HIV counseling and testing. Methods A cross-sectional study was carried out comprising 1,658 mothers living in Porto Alegre, Brazil. Biological, reproductive and social variables were obtained from mothers by means of a standardized questionnaire. Being … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
19
1
7

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 11 publications
6
19
1
7
Order By: Relevance
“…In the post-test upon diagnosis, counseling had been recognized by 20 (51.2%) interlocutors. A small percentage of patients who reported having received counseling was also observed in cross-sectional survey conducted by Goldani et al 7 in Porto Alegre -RS, with 1603 women tested during pregnancy, from which only 39.2% reported having been counselled about the test. The authors found that there was a greater chance of not receiving counseling among low-income pregnant women and who initiated prenatal tests belatedly.…”
Section: Hivtest Advice and Ethical Aspectssupporting
confidence: 55%
“…In the post-test upon diagnosis, counseling had been recognized by 20 (51.2%) interlocutors. A small percentage of patients who reported having received counseling was also observed in cross-sectional survey conducted by Goldani et al 7 in Porto Alegre -RS, with 1603 women tested during pregnancy, from which only 39.2% reported having been counselled about the test. The authors found that there was a greater chance of not receiving counseling among low-income pregnant women and who initiated prenatal tests belatedly.…”
Section: Hivtest Advice and Ethical Aspectssupporting
confidence: 55%
“…Este resultado é inferior ao encontrado por Veloso et al 18 em inquérito nacional realizado com puérperas, em que cerca de 14% referiam ter sido testadas sem seu conhecimento ou autorização, mas semelhante ao verificado em estudos na Região Sul do país. 22,23 Problemas no aconselhamento também têm sido identificados no momento da admissão para o parto. 24 Em relação à sífilis, embora os instrumentos adotados não contivessem dados sobre o aconselhamento pré e pós-teste, a falta de informação sobre a solicitação e/ou realização do exame e o desconhecimento de resultados de exames positivos revelam também problemas nessa abordagem.…”
Section: Discussionunclassified
“…In this way, they tend to provide more information during hospital procedures, including the time when the HIV rapid test is performed in this population. In contrast, a study on anti-HIV tests performed prior to delivery, conducted in the city of Porto Alegre, showed that the absence of prenatal care, the use of the HIV rapid test, multiparity and low income increased the chance of non-counseling 17 . Low-income women were expected to receive more care and, consequently, more counseling from the health team.…”
mentioning
confidence: 93%